(untitled) (American International Journal of Sciences and Engineering Research, 2022)
The objective of this research is set to produce energy by utilizing the unused heat of gas stove through thermoelectric generator. Currently, an increasing concern of environmental issues of emissions like greenhouse effects and the scarcity of fossil fuel has resulted in extensive research into the alternative ways of generating electrical power. Thermoelectric power generator has been considering as one of the promising alternatives due to its advantages. The application of this alternative option in converting waste-heat energy directly into electrical power that may also enhance the overall efficiencies of energy conversion systems. In this study, a gas burner was set to generate electricity that will produce waste heat. One thermoelectric unit is installed underneath the burner cap of the gas burner. Gas flame at the edge of the burner cap creates heat sources (hot side) for the thermoelectric unit. A gas-mixing chamber underneath the thermoelectric unit functions as heat sink (cold side) for the thermoelectric unit. An insulation plate is inserted in between the thermoelectric unit and the burner cap to control the hot side temperature. The thermoelectric unit generates electricity while the gas burner is in use and the flame heats up the burner cap. The thermoelectric unit connects to an electric circuit and provides electricity to power devices. JEL Classification Codes: Q41, Q42, Q43, Q56.